Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Connect with a community of experts ready to provide precise solutions to your questions quickly and accurately. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

Describe how the graph of the parent function [tex]\( y = \sqrt{x} \)[/tex] is transformed when graphing [tex]\( y = -3 \sqrt{x-6} \)[/tex].

Sagot :

Certainly! Let's break down the transformations for the function [tex]\(y = -3\sqrt{x-6}\)[/tex] from the parent function [tex]\(y = \sqrt{x}\)[/tex].

1. Translation:

The function [tex]\(y = \sqrt{x}\)[/tex] is modified to [tex]\(y = \sqrt{x-6}\)[/tex]. The expression [tex]\(x-6\)[/tex] inside the square root indicates a horizontal translation. Specifically, we replace [tex]\(x\)[/tex] with [tex]\(x-6\)[/tex], which shifts the graph to the right by 6 units.

2. Reflection:

The next transformation involves a reflection. The function [tex]\(y = \sqrt{x-6}\)[/tex] becomes [tex]\(y = -\sqrt{x-6}\)[/tex]. The negative sign in front of the square root indicates that the graph is reflected across the x-axis. This means that if a point [tex]\( (a, b) \)[/tex] on the original graph becomes [tex]\( (a, -b) \)[/tex].

3. Vertical Scaling:

Finally, the function [tex]\(y = -\sqrt{x-6}\)[/tex] is modified to [tex]\(y = -3\sqrt{x-6}\)[/tex]. The coefficient [tex]\(-3\)[/tex] outside the square root indicates a vertical scaling by a factor of 3, combined with a reflection (due to the negative sign). Vertical scaling by a factor of 3 means that the graph is stretched by a factor of 3 in the vertical direction.

Combining all these individual transformations step-by-step:

- The parent function [tex]\(y = \sqrt{x}\)[/tex] is translated 6 units to the right.
- The translated function [tex]\(y = \sqrt{x-6}\)[/tex] is then reflected across the x-axis resulting in [tex]\(y = -\sqrt{x-6}\)[/tex].
- Lastly, the reflected function [tex]\(y = -\sqrt{x-6}\)[/tex] is vertically scaled by a factor of 3 to become [tex]\(y = -3\sqrt{x-6}\)[/tex].

Therefore, the graph of [tex]\(y = \sqrt{x}\)[/tex] is transformed to [tex]\(y = -3\sqrt{x-6}\)[/tex] by:
1. Translating 6 units to the right.
2. Reflecting across the x-axis.
3. Vertically scaling by a factor of [tex]\(-3\)[/tex].

These combined transformations provide the complete graphing of the function [tex]\(y = -3\sqrt{x-6}\)[/tex].